TikTok-Based Learning Media for Enhancing Elementary Students’ Digital Literacy in Coding and AI Education - Nur Fahmi Akhmad; Mujaddid; Jufri (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
This study aims to develop and evaluate TikTok-based learning media to improve elementary school students’ digital literacy in Coding and Artificial Intelligence (AI) learning. The research employed a Research and Development (R&D) approach using the Four-D (Define, Design, Develop, and Disseminate) model. The study was conducted at UPTD SDN 239 Inpres Nipa, Maros Regency, involving 35 fifth-grade students selected through purposive sampling. Data were collected using questionnaires, expert validation instruments, and pretest–posttest assessments, and analyzed using descriptive and comparative statistical techniques. The results indicate that the developed learning media achieved very high validity, with average scores of 3.82 for content validation and 3.89 for media design validation. Practicality testing through small-scale field trials yielded a 92.5% positive student response rate, categorized as very practical. Effectiveness testing demonstrated a significant improvement in students’ learning outcomes and digital literacy skills. The experimental group using TikTok-based learning media showed a mean score increase from 62.06 (pretest) to 85.89 (posttest), which was notably higher than that of the control group taught using conventional methods. These findings suggest that TikTok-based microlearning media are effective in enhancing students’ digital literacy, computational thinking, and understanding of basic Coding and AI concepts at the elementary school level. This study provides empirical evidence for integrating social media platforms as innovative learning media in digital literacy-oriented education.